Construction of an attenuated Salmonella enterica serovar Paratyphi A vaccine strain harboring defined mutations in htrA and yncD. (August 2015) - Zhu, Chunyue; Xiong, Kun; Chen, Zhijin; Hu, Xiaomei; Li, Jianhua; Wang, Yiran; Rao, Xiancai; Cong, Yanguang
Abstract The global epidemic features of enteric fever have changed greatly in recent years. The incidence of enteric fever caused by Salmonellaenterica serovar Paratyphi A has progressively increased. In some areas of Asia, infections with S. Paratyphi A have exceeded those with S. Typhi, resulting in S. Paratyphi A becoming the main causative agent of enteric fever. However, two currently licensed typhoid vaccines do not confer adequate cross‐protection against S. Paratyphi A infection. Therefore, development of specific vaccines against enteric fever caused by S. Paratyphi A is urgently needed. In the present study, an attenuated strain was constructed by double deletion of the htrA and yncD genes in a wild‐type strain of S. Paratyphi A and its safety and immunogenicity assessed. In a mouse model, the 50% lethal dose of the double deletion mutant and the wild‐type strain were 3.0 × 108 CFU and 1.9 × 103 CFU, respectively, suggesting that the double deletion resulted in remarkably decreased bacterial virulence. Bacterial colonization of the double deletion mutant in the livers and spleens of infected mice was strikingly less than that of the wild‐type strain. A single nasal administration of the attenuated vaccine candidate elicited high concentrations of anti‐LPS and anti‐flagellin IgG in a mouse model and protected immunized mice against lethal challenge with the wild‐type strain. Thus, our findings suggest that the attenuated vaccine strain is a promising candidate worthy of further evaluation both as a human enteric fever vaccine and as a vaccine delivery vector for heterologous antigens.